STUDI TERKAIT DENGAN STANDAR PENGENDALIAN MUTU DAN KUALITAS AUDIT - Hisar Pangaribuan; Jenny Sihombing; Ifki Putri Dwi Nanda Dutrianda (Jurnal Ekonomis, 2020)
The aim of this study is to examine the effect implementation of audit quality control system in audit engangement on audit quality. The data collected for processing is obtained from the questionnaires distributed to auditors who have performed their professional duties as auditors (with minimum as a senior auditor). Statistical data processing is carried out for hypothesis testing in making conclusions using a variance-based approach. The Audit quality control system is a crucial thing in increasing user confidence in the attestation services provided by public accounting firms. The standards of quality control are useful to ensure the quality of the resulting audit can meet the objectives and specifications that have been previously set. When quality control systems are implemented properly, it will have a significant effect on improving the resulting audit quality. The three most important things in determining an adequate quality control system are the attitude of auditor independence, continuing professional education and the principle of prudence in engagement. The results of this study will be very useful for auditors in carrying out their duties so that audit quality is properly maintained.